2021
DOI: 10.1021/acs.jpcb.1c05013
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulations of Bimolecular Electron Transfer: the Distance-Dependent Electronic Coupling

Abstract: Understanding the distance dependence of the parameters underpinning Marcus theory is imperative when interpreting the results of experiments on electron transfer (ET). Unfortunately, most of these parameters are difficult or impossible to access directly with experiments, necessitating the use of computer simulations to model them. In this work, we use molecular dynamics simulations in conjunction with constrained density functional theory calculations to study the distance dependence of the electronic coupli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 87 publications
0
14
0
Order By: Relevance
“…Hence, electron transfer from the stabilized halide occurs by tunneling through the halide-sequestering tmam ligand. While direct contact between the donor and acceptor promotes electronic coupling, 71 the tmam ligand is formally reduced in the excited state and therefore does not provide strong coupling to the acceptor orbital predominantly localized on the metal and cyclometallating ligands. 72 , 73 Indeed, prior reductive quenching studies reported no measurable kinetic difference when an electron donor was covalently tethered proximal or distal to the ligand formally reduced in the excited state.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, electron transfer from the stabilized halide occurs by tunneling through the halide-sequestering tmam ligand. While direct contact between the donor and acceptor promotes electronic coupling, 71 the tmam ligand is formally reduced in the excited state and therefore does not provide strong coupling to the acceptor orbital predominantly localized on the metal and cyclometallating ligands. 72 , 73 Indeed, prior reductive quenching studies reported no measurable kinetic difference when an electron donor was covalently tethered proximal or distal to the ligand formally reduced in the excited state.…”
Section: Discussionmentioning
confidence: 99%
“…Bottom: examples of Pe .– /DMA .+ conformations in acetonitrile with the same r COM = 0.85 nm but with small (left) and large (right) V values. Adapted with permission from ref . Copyright 2021 American Chemical Society.…”
Section: The Coupling and The Distancementioning
confidence: 99%
“…Simulations of the quenching dynamics using MD is certainly a promising approach. After early works in the 90s, MD simulations were recently applied again to bimolecular ET processes to obtain information that are not easily accessible experimentally. ,, They concerned the estimation of ΔG CS as well as the distance dependence of V mentioned above. , As the reorganization energy can also be obtained from MD simulations, the ET probability can in principle be calculated from Marcus theory. However, the latter is only valid for nonadiabatic ET, i.e.…”
Section: The Coupling and The Distancementioning
confidence: 99%
“…All of these problems are in their native environments and three-dimensional in nature and thus would benefit from the application of the technique described here. In addition, this technique’s unprecedented coupling of 3D spatial and orientational information at high time resolution points to future experiments to probe intramolecular dynamics, such as electron transfer reactions, in heterogeneous systems. This may, in the future, give unprecedented insight into orientation-dependent chemical dynamics in systems that may themselves be spatially and dynamically complex.…”
Section: Discussionmentioning
confidence: 99%
“…Orientation is a quantity that can have an intimate impact on reactivity . To give but one example, the electronic coupling parameter which modulates an electron transfer reaction is orientation dependent. Orientation can also function as a sensitive reporter on the nanoscale environment, with previous work in bulk and at the single-particle level probing such a quantity. This is relevant in complex systems such as cells, where the local environment can vary strongly with time and positionalso potentially affecting chemical dynamics.…”
Section: Introductionmentioning
confidence: 99%